The use of proxies and proxy-reported measures: a report of the international society for quality of life research (ISOQOL) proxy task force - Roydhouse, Jessica K.; Cohen, Matthew L.; Eshoj, Henrik R.; Corsini, Nadia; Yucel, Emre; Rutherford, Claudia; Wac, Katarzyna; Berrocal, Allan; Lanzi, Alyssa; Nowinski, Cindy; Roberts, Natasha; Kassianos, Angelos P.; et al. (My University, 2021)
Aims: Proxy reports are often used when patients are unable to self-report. It is unclear how proxy measures are currently in use in adult health care and research settings. We aimed to describe how proxy reports are used in these settings, including the use of measures developed specifically for proxy reporting in adult health populations. Methods: We systematically searched Medline, PsycINFO, PsycTESTS, CINAHL and EMBASE from database inception to February 2018. Search terms included a combination of terms for quality of life and health outcomes, proxy-reporters, and health condition terms. The data extracted included clinical context, the name of the proxy measure(s) used and other descriptive data. We determined whether the measures were developed specifically for proxy use or were existing measures adapted for proxy use. Results: The database search identified 17,677 possible articles, from which 14,098 abstracts were reviewed. Of these, 11,763 were excluded and 2335 articles were reviewed in full, with 880 included for data extraction. The most common clinical settings were dementia (30%), geriatrics (15%) and cancer (13%). A majority of articles (51%) were paired studies with proxy and patient responses for the same person on the same measure. Most paired studies (77%) were concordance studies comparing patient and proxy responses on these measures. Discussion: Most published research using proxies has focused on proxy-patient concordance. Relatively few measures used in research with proxies were specifically developed for proxy use. Future work is needed to examine the performance of measures specifically developed for proxies. Systematic review registration: PROSPERO No. CRD42018103179
Keywords: Proxy measures; Proxy-reported outcomes; Outcome measures; Quality of life; Systematic review